Against the law. Labor protests in China's Rustbelt and Sunbelt - Kwan Lee, Ching (Berkeley, 2007)
"This study opens a critical perspective on the slow death of socialism and the rebirth of capitalism in the world's most dynamic and populous country. Based on remarkable fieldwork and extensive interviews in Chinese textile, apparel, machinery, and household appliance factories, Against the Law finds a rising tide of labor unrest mostly hidden from the world's attention. Providing a broad political and economic analysis of this labor struggle together with fine-grained ethnographic detail, the book portrays the Chinese working class as workers' stories unfold in bankrupt state factories and global sweatshops, in crowded dormitories and remote villages, at street protests as well as in quiet disenchantment with the corrupt officialdom and the fledgling legal system."